Ligand Migration from Cluster to Support: A Crucial Factor for Catalysis by Thiolate‐protected Gold Clusters. Issue 23 (26th November 2018) - Zhang, Bei; Sels, Annelies; Salassa, Giovanni; Pollitt, Stephan; Truttmann, Vera; Rameshan, Christoph; Llorca, Jordi; Olszewski, Wojciech; Rupprechter, Günther; Bürgi, Thomas; Barrabés, Noelia
Abstract: Thiolate protected metal clusters are valuable precursors for the design of tailored nanosized catalysts. Their performance can be tuned precisely at atomic level, e. g. by the configuration/type of ligands or by partial/complete removal of the ligand shell through controlled pre‐treatment steps. However, the interaction between the ligand shell and the oxide support, as well as ligand removal by oxidative pre‐treatment, are still poorly understood. Typically, it was assumed that the thiolate ligands are simply converted into SO2, CO2 and H2 O. Herein, we report the first detailed observation of sulfur ligand migration from Au to the oxide support upon deposition and oxidative pre‐treatment, employing mainly S K‐edge XANES. Consequently, thiolate ligand migration not only produces clean Au cluster surfaces but also the surrounding oxide support is modified by sulfur‐containing species, with pronounced effects on catalytic properties. Abstract : A rolling stone gathers no moss : The fate of the protecting ligand shell of thiolate gold clusters upon catalyst preparation was revealed for the first time, utilizing XAFS. Both the pre‐treatment temperature and support oxide influence the ligand migration from clusters to the support. The ligand transformation to SOx species plays an important role and should not be neglected when interpreting catalytic data.